Jean Baudrillard. „Socjologia” i poetyka - Wójcik, Tomasz (Załącznik Kulturoznawczy, 2021)
The sketch is an attempt at a structured reflection concerning the issue of the presence of literature in the writings of Jean Baudrillard (various forms and meanings of this presence). It complements the books by Agnieszka Ogonowska Twórcze metafory medialne. Baudrillard – McLuhan – Goffman and Michał Kłosiński Ratunkiem jest tylko poezja. Baudrillard – Teoria – Literatura, and at the same time it outlines the possibilities of further research on this issue (especially in the genology of writings by the French sociologist).